An integrative study on the green cultural industry and its determinants in Jiangsu province, China under the cultural revitalization initiative: a global perspective - Ding, Yaoyao; Zhang, Rong; Zou, Yuntao (Frontiers in Psychology, 2024)
The cultural industry stands as a pivotal element of sustainable economics. This study adopts a holistic perspective to analyze Jiangsu Province's cultural industry, revealing its prominent national stature but suboptimal economic returns, characterized by diminishing scale benefits. Key challenges include low scale efficiency and smaller enterprise sizes, exacerbated by the province's subpar urbanization trajectory. Drawing on these insights, targeted recommendations are proposed. The comprehensive evaluation approach used, emphasizing contrasts with comparable sectors, offers applicability across various research domains.